PENGARUH KUALITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN SISTEM PENGENDALIAN INTERN TERHADAP KETEPATWAKTUAN PELAPORAN KEUANGAN PEMERINTAH DESA - Marlinawati Marlinawati; Dewi Kusuma Wardani (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
The purpose of this research is to know the influence between the Quality of Human Resources, Utilization of Information Technology and Internal ControlSystem Against Timeliness of Village Government Financial Reporting at Gunungkidul Regency. This research is causative research. The population isthe village government in Gunungkidul Regency, especially in Gedangsari subdistrict. Criteria of respondents in the study were to village and village apparatus. We use questionnaire to collect data. We use multiple regression with SPSS program version 16.0 to analyze data. We find that quality of human resources and internal control system have a positive influence on the timeliness of village government financial reporting. On the other hand, utilization of information technology does not influence the timeliness of village government financial reporting. These imply that the quality of human resources and internal control system can speed up the preparation of village government financial reporting.